Analisis Forensik Aplikasi TikTok Pada Smartphone Android Menggunakan Framework Association of Chief Police Officers - Fitri Anggraini; Herman Herman; Anton Yudhana (JURIKOM (Jurnal Riset Komputer), 2022)
TikTok is the most popular social media app that ranks sixth in the world in January 2022 according to We Are Media & Hootsuite. Along with the increasing number of uses of this application, the negative impacts it causes are also increasing, ranging from fraud, cyberbullying, to the spread of fake news (hoax). This study focuses on the negative impact of defamation. The purpose of the research is to plan and implement a digital forensics process using the Association of Chief Police Officers (ACPO) framework to raise evidence of defamation cases on the TikTok application. The forensic process is carried out in the form of static forensics on cases that are intentionally made in the form of simulating TikTok postings using an android smartphone. This research combines the ACPO forensics framework with the Magnet Axiom forensics tools. The combination of the two succeeded in raising 77% of evidence in the form of data messages, videos, and hashtags. Where these data have been previously defined as initial data posted in the simulation process